Shakespeare and Consciousness - Budra, Paul.; Werier, Clifford; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book examines how early modern and recently emerging theories of consciousness and cognitive science help us to re-imagine our engagements with Shakespeare in text and performance. Papers investigate the connections between states of mind, emotion, and sensation that constitute consciousness and the conditions of reception in our past and present encounters with Shakespeare's works. Acknowledging previous work on inwardness, self, self-consciousness, embodied self, emotions, character, and the mind-body problem, contributors consider consciousness from multiple new perspectives-as a phenomenological process, a materially determined product, a neurologically mediated reaction, or an internally synthesized identity-approaching Shakespeare's plays and associated cultural practices in surprising and innovative ways.
Introduction: Paul Budra and Clifford Werier -- I: Consciousness, Cognitive Science, and Character -- Consciousness and Cognition in Shakespeare and Beyond, Clifford Werier -- Shakespeare Studies and Consciousness, Edward Pechter -- Hamlet in the Bat Cave, Paul Budra -- II: Consciousness and Theatrical Practice -- King of Shadows: Early Modern Characters and Actors, Amy Cook -- The Distributed Consciousness of Shakespeare's Theatre, Laurie Johnson -- Minds at work: writing, acting, watching, reading Hamlet, Ros King -- III: Consciousness and the Body -- "Being Unseminared": Pleasure, Instruction, and Playing the Queen in Anthony and Cleopatra, Andrew Brown -- Bodies and Selves: Autoscopy, Out-of-Body Experiences, Mind-Wandering and Early Modern Consciousness, Jan Purnis -- Hamlet and Time-Consciousness: A Neurophenomenological Reading, Matthew Kibbee -- IV: Consciousness, Emotion, and Memory -- Shylock's Shy Conscience: Consciousness, Power and Conversion in The Merchant of Venice, Tiffany Hoffman -- Forgetting Cleopatra, Elizabeth Hodgson -- Notes on the Contributors.
Keywords: European literature; Consciousness; Early Modern/Renaissance Literature; Cognitive Psychology